Implementasi Kebijakan Pencegahan dan Penanggulangan HIV/AIDS di Kota Palangka Raya Provinsi Kalimantan Tengah - Nurhasanah Nurhasanah; Yuliana Yuliana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The purpose of this study is to determine the implementation of the HIV/AIDS Prevention and Prevention Policy in Palangka Raya City, Central Kalimantan Province. The method used in this study is a qualitative method with observation, interview, and documentation techniques. The data sources in this study were employees of the Health Office and Community of the City of Palangka Raya. The results showed that the implementation of the HIV/AIDS Prevention and Control Policy in Palangka Raya City was not in accordance with what was stated in Regional Regulation Number 8 of 2011. The Health Office had handled the infected people to the maximum. Handling is carried out, namely starting from socialization, control and rehabilitation efforts. The Health Office has not fully carried out socialization among the people of the City of Palangka Raya, there is still no satisfactory cooperation between institutions and organizations formed for the problem of prevention and control of HIV/AIDS. The obstacles that hamper the Office of Health in implementing are the lack of facilities and infrastructure such as special remedies, funding issues, and workers who are ready to implement the HIV/AIDS prevention and prevention program